Origin of the zinc-lead ore deposit Topla and its particularities - Drovenik, Matija; Pungartnik, Mihael (Geologija, 1987)
In the northem Karavanke besides the zinc-lead ore deposit Mežica with orebodies predominantly in Ladinian limestones and dolomites there is also the zinc-lead deposit Topla, where Anisian dolomite is mineralized. In the Topla deposit the carbonate mud which was later dolomitized was deposited in three separated shallow trough in the upper tidal zone. Into the carbonate mud arrived clay minerals and metal compounds. During diagenesis iron sulfides, sphalerite and galena crystallized. In such a way three concordant orebodies originated. Ore minerals and dolomite have been mobilized several times during epigenesis and retrograde epigenesis. The paper deals with particularities of orebodies as well as with detailed analysis of the origin and transformations of ore from Anisian up to present.